Towering above: an interpretation of the Late Iron Age architecture at Toftum Næs, Denmark - Jessen, Mads Dengsø; Terkildsen, Kamilla Fiedler (Danish Journal of Archaeology, 2016)
The newly excavated sites of Toftum Næs, Jutland (Denmark), will be presented, and the special features that have been registered here will be discussed. In particular, the conspicuous architecture will figure prominently; a very sturdily built and thus high structure that can only be interpreted as a tower placed along with a succession of larger hall-type buildings, and a possible ritual building. This ‘aristocratic quarter’ is in direct contact with another area characterized by a larger pit-house cluster of more the 100 units, and placed in the vicinity of two conjoining streams. The different structures mentioned and their internal, topographical distribution as well as architectural features will be incorporated as the main base for a functional interpretation of and motive behind the buildings and the activities pertaining to the site in general. The topic of commercial control and what type of influence the aristocracy had on the early development on these types of sites will be included. Furthermore, the structural fluctuation of the site at Toftum Næs, and in particular the changes that seem to have taken place during the main use-phase both at the site in question and with regard to the overall development of aristocratic sites with production areas and at the Viking Age towns, will be debated in this paper.